Fur-type transcriptional repressors and metal homeostasis in the cyanobacterium Synechococcus sp. PCC 7002 - Ludwig, Marcus; Chua, Tiing Tiing; Chew, Chyue Yie; Bryant, Donald A. (Frontiers in Microbiology, 2015)
Metal homeostasis is a crucial cellular function for nearly all organisms. Some heavy metals (e.g., Fe, Zn, Co, Mo) are essential because they serve as cofactors for enzymes or metalloproteins, and chlorophototrophs such as cyanobacteria have an especially high demand for iron. At excessive levels, however, metals become toxic to cyanobacteria. Therefore, a tight control mechanism is essential for metal homeostasis. Metal homeostasis in microorganisms comprises two elements: metal acquisition from the environment and detoxification or excretion of excess metal ions. Different families of metal-sensing regulators exist in cyanobacteria and each addresses a more or less specific set of target genes. In this study the regulons of three Fur-type and two ArsR-SmtB-type regulators were investigated in a comparative approach in the cyanobacterium Synechococcus sp. PCC 7002. One Fur-type regulator controls genes for iron acquisition (Fur); one controls genes for zinc acquisition (Zur); and the third controls two genes involved in oxidative stress (Per). Compared to other well-investigated cyanobacterial strains, however, the set of target genes for each regulator is relatively small. Target genes for the two ArsR-SmtB transcriptional repressors (SmtB (SYNPCC7002_A2564) and SYNPCC7002_A0590) are involved in zinc homeostasis in addition to Zur. Their target genes, however, are less specific for zinc and point to roles in a broader heavy metal detoxification response.